2021
DOI: 10.1002/suco.202000788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural rubber latex on the shrinkage behavior and porosity of geopolymer concrete

Abstract: Shrinkage‐reducing admixture has been proved as the best solution to reduce the shrinkage cracks on the surface of the concrete. Various shrinkage‐reducing admixtures available in the local market are chemical, highly hazardous, and limited use in concrete. In the present research, rubber latex was used by replacing water up to 2% in geopolymer concrete. Volumetric shrinkage for geopolymer concrete with different doses of rubber latex was determined and compared those results with traditional cement concrete o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Water absorption decreased with an increase in FPRL contents due to water in FPRL contributing free water in the geopolymer matrix. This trend was similar to the findings of Rath et al [45], where geopolymer concrete mixed with rubber latex exhibited decreased water absorption. It can be concluded that rubber latex at a higher percentage seals the pores on the surface of the samples to prevent water from entering inside.…”
Section: Figure 12 Percentage Of Water Absorption In Geopolymer Morta...supporting
confidence: 91%
“…Water absorption decreased with an increase in FPRL contents due to water in FPRL contributing free water in the geopolymer matrix. This trend was similar to the findings of Rath et al [45], where geopolymer concrete mixed with rubber latex exhibited decreased water absorption. It can be concluded that rubber latex at a higher percentage seals the pores on the surface of the samples to prevent water from entering inside.…”
Section: Figure 12 Percentage Of Water Absorption In Geopolymer Morta...supporting
confidence: 91%
“…As a result of the study, it was stated that the shrinkage of GC is much lower than that of PCC. In addition, it was stated that by adding 2% rubber latex to the GC, the shrinkage could be reduced by 83% compared to the PCC 69 . Drying shrinkage of geopolymer mortar generally increased up to 28 days, but then it started to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was stated that by adding 2% rubber latex to the GC, the shrinkage could be reduced by 83% compared to the PCC. 69 Drying shrinkage of geopolymer mortar generally increased up to 28 days, but then it started to decrease. In this study, the first swelling occurred in 50FA50GGBS-0.35 mortar and 50FA50GGBS-0.33 mortar at 14 and 28 days, respectively, while it occurred at 56 days in all other geopolymer mortar.…”
Section: Drying Shrinkagementioning
confidence: 98%
“…It was found that the addition of organic admixtures can reduce the water loss and improve the hydrophobicity of pore walls, which effectively reduced the capillary pressure and increased the internal relative humidity, thereby alleviating the autogenous shrinkage by about 70% for alkaliactivated materials [16]. Rath et al [17] investigated the effect of organic rubber latex on the pore structure and capillary suction of geopolymer concrete and found that the addition of organic rubber latex can effectively decrease the early-age shrinkage of geopolymers. Huang et al [18] reported that the use of edible oil can reduce the surface tension of concrete and make its internal structure denser, thereby effectively reducing the autogenous shrinkage of concrete by 68% without obvious strength loss.…”
Section: Introductionmentioning
confidence: 99%